Pengaruh Faktor Individu, Faktor Lingkungan dan Perilaku Kewirausahaan Terhadap Kinerja Usahatani Jamur Tiram di Kota Payakumbuh - Ernanda, Revi; Sumbari, Chika (Journal Galung Tropika, 2021)
The purpose of this research was to analyze the effect of individual factors, enviromental factors, entrepreneurial behavior on the performance of oyster mushroom farming in Payakumbuh city. This research was conducted in Mei – November 2020, and the number of respondents was 60 farmers. The analysis method used was quantitive analysis using Partial Least Square (PLS). The results showed the performance of oyster mushroom farming was determined by entrepreneurial behavior with a coefficient of influence coefficient 0.535. the most dominant entrepreneurial behavior is responsiveness to opportunities (?) of 0.877. Entrepreneurial behavior is influenced by individual factors with an influence coefficient 0.621. The most dominant individual factor that reflected entrepreneurial behavior was the self convidence with the load factor (?) 0.827. Individual factors are influenced by environmental factors with influence coefficient 0.367. The most dominant environmental factor that affected entrepreneurial behavior was inputs availability with the load factor (?) 0.800. This show that an increase of entrepreneurial behavior will be improve performance perspective of oyster mushroom in Payakumbuh city.